2016
DOI: 10.1007/s00221-016-4795-1
|View full text |Cite
|
Sign up to set email alerts
|

Foreknowledge of an impending startling stimulus does not affect the proportion of startle reflexes or latency of StartReact responses

Abstract: During a simple reaction time (RT) task, movements can be initiated early and involuntarily through presentation of a loud startling acoustic stimulus (SAS), a phenomenon termed the StartReact effect. In order to infer that activity in startle-related structures led to the early response triggering, it is important to observe a concurrent startle reflex in sternocleidomastoid. It is generally accepted that to consistently elicit a startle reflex, the SAS must be both intense and unpredictable. However, it rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Carlsen and collaborators studied the influence of startle in motor readiness and concluded that a startling stimulus represents the trigger for a faster release of previously prepared movements (Carlsen et al, 2011). Furthermore, a more recent study from his laboratory supported the physiological independence of startle reflex from the mechanism of response preparation (Drummond, Leguerrier, & Carlsen, 2016). Nonetheless, also in this study the direction of the startle RT effect was in line to the classic intensity effect (i.e., fastening RT) and opposite to our results.…”
Section: Discussionmentioning
confidence: 98%
“…Carlsen and collaborators studied the influence of startle in motor readiness and concluded that a startling stimulus represents the trigger for a faster release of previously prepared movements (Carlsen et al, 2011). Furthermore, a more recent study from his laboratory supported the physiological independence of startle reflex from the mechanism of response preparation (Drummond, Leguerrier, & Carlsen, 2016). Nonetheless, also in this study the direction of the startle RT effect was in line to the classic intensity effect (i.e., fastening RT) and opposite to our results.…”
Section: Discussionmentioning
confidence: 98%